PEMANFAATAN DAN PENGEMBANGAN BLOG SEBAGAI MEDIA DAN SUMBER BELAJAR PADA MATA PELAJARAN FIQIH TINGKAT MADRASAH TSANAWIYAH - Yusuf Amin Nugroho (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
In order to actualize creative learning meaningful, a teacher must be smart in choosing the media, determine the method, and also motivate students to utilize media and learning resources. Many media and learning resources that can be utilized to support the success of students in school uniform jurisprudence (MTs), one of which is to utilize the internet media. The purpose of this research to provide the knowledge and practical measures related to the utilization and development of blogs as a media and learning resources jurisprudence on the level of MTs. Hopefully, this study can provide inspiration and motivation for teachers in the school to design learning strategies that are more meaningful for the students, one of them made the blog as a media and learning resources. This research includes developmental research combined with library research, the aim is to develop, expand and dig deeper into the theory about the use and development of blogs as a source of study subjects Fiqih MTs level, also explains the steps to create a blog to be used as a media and appropriate learning resources. Development blog itself could do with providing exciting content students need, easily understood navigation, link your blog with social media, provide links to sites that are important, pay attention to readability, and practice search engine optimation (SEO).Extra blog as media and learning resources jurisprudence MTs ultimate level that makes learning more interesting, fun, make students active learning, interactive and flexible, student motivation and be a means for directing students to use the Internet more intelligent. The weakness is the limitation of infrastructure, increasing teacher workload, and fragility of misunderstanding in receiving information. Media and blog-based learning resources are also less suitable to improve the competence of affective, and hence learning fiqih face-to-face is still needed.